A New Perspective on Relativity Theory (Global Journal of Science Frontier Research, 2024)
The particular theory of relativity was created by Albert Einstein in 1905 As the starting point for this theory he adopted two principles from the beginning the principle of relativity and the principle of the constancy of the velocity of light Later when it was pointed out that the velocity of light changes within the solar system in a gravitational field he argued that the velocity of light does not appear to be constant due to the spatial distortion He then constructed the general theory of relativity that took into account the spatial distortion
Keywords: particular relativity theory; general relativity theory